Heat wave induces oxidative damage in the Chinese pond turtle (Mauremys reevesii) from low latitudes - Tao, Weijie; Ou, Junwei; Wu, Danyang; Zhang, Qiong; Han, Xingzhi; Xie, Lei; Li, Shuran; Zhang, Yongpu (Frontiers in Ecology and Evolution, 2022)
Introduction Global warming has led to frequent heat waves, causing global organisms to face severe survival challenges. However, the way in which heat waves threaten the fitness and survival of animals remains largely unclear. Oxidative damage and immunity are widely considered the link between heat waves and threats to animals. Methods To evaluate the oxidative damage caused by heat waves and to reveal the physiological resistance to heat waves by the antioxidant defense of animals from different latitudes, we exposed both high-latitude (Zhejiang) and low-latitude (Hainan) populations of Chinese pond turtle (Mauremys reevesii) to simulate heat waves and a moderate thermal environment for 1 week, respectively. Next, we compared the oxidative damage by malondialdehyde (MDA) and antioxidant capacity by superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and total antioxidant capacity (T-AOC) in the liver tissues and evaluated the innate immunity by serum complement protein levels (C3, C4) and lysozyme activity in plasma of turtles. Results and discussion We found that heat waves significantly increased the content of MDA and the activity of CAT, whereas it decreased the activity of SOD, T-AOC, and GSH/GSSG in turtles from low latitudes. Furthermore, heat waves increased CAT activity but decreased GSH/GSSG in turtles from high latitudes. Although the turtles from high latitudes had higher levels of innate immunity, the heat waves did not affect the innate immunity of C3, C4, or lysozyme in either population. These results indicate that the low-latitude population suffered higher oxidative damage with lower antioxidant capacities. Therefore, we predict that Chinese pond turtles from low latitudes may be more vulnerable to heat waves caused by climate warming. This study reveals the physiological and biochemical resistance to heat waves in Chinese pond turtles from different latitudes and highlights the importance of integrative determination of fitness-related responses in evaluating the vulnerability of ectotherms from different latitudes to climate warming.